Coating biodegradable magnesium alloys with electrospun poly-L-lactic acid-åkermanite-doxycycline nanofibers for enhanced biocompatibility, antibacterial activity, and corrosion resistance - Bakhsheshi-Rad, H. R. (Elsevier B. V., 2019)
Magnesium alloys are attracting increasing attention for orthopedic applications on account of their superior biocompatibility and biodegradability. However, such applications have been limited by their high degradation rate and inadequate antibacterial performance. The present study illustrates the use of a poly-L-lactic acid (PLLA)-åkermanite (AKT)-doxycycline (DOXY) nanofiber coating, created using the electrospinning method, to enhance the corrosion resistance, antibacterial performance, and cytocompatibility of Mg alloys. The experimental results show the PLLA-based nanofiber coatings are smooth and uniform with fiber diameters ranging from 300 to 350 nm. PLLA nanofibers containing AKT have a higher bonding strength (11.8 MPa) than PLLA nanofibers, owing to the significant effect of AKT on the PLLA structure. An in vitro drug release profile of PLLA-AKT nanofibers containing DOXY shows that the nanofibers allow rapid release of drug in the initial stage to provide antibacterial effects as well as sustained release over the long term to prevent infection. The implants coated with PLLA-AKT nanofibers containing DOXY have excellent antibacterial performance against Gram-positive (Staphylococcus aureus, ATCC 12600) and Gram-negative (Escherichia coli, ATCC 9637) bacteria; those coated with PLLA and PLLA-AKT without DOXY have poor antibacterial performance. Cytotoxicity tests show that PLLA and PLLA-AKT nanofiber coatings considerably enhance the cytocompatibility of Mg alloys, while incorporation of a high concentration of DOXY (10% wt.) into the PLLA-AKT coating has adverse effects on cytocompatibility. Thus, PLLA-AKT nanofiber coatings containing low concentrations of DOXY can be employed to control the degradation rate and enhance the antibacterial performance and biocompatibility of Mg alloys as applied to bone infection treatments. The results of this study represent essential information to direct the development of future orthopedic applications.